On the nucleons motion in the nucleus as being due to realistic inter-nucleonic forces - Lyakhno, Yu.P. (Вопросы атомной науки и техники, 2017)
This paper deals with the possible motion of nucleons in the nucleus, which is due to realistic inter-nucleonic forces. This approach provides new or more substantiated conclusions about the nuclear structure than those based on the effective interaction of nucleons, while the shell model of the nucleus may lead to questionable conclusions regarding the nuclear structure and nuclear reaction mechanisms.